Safety and immunogenicity of mRNA COVID‐19 vaccine in inpatients with muscular dystrophy. Issue 2 (19th December 2022) - Saito, Tomoko; Saito, Toshio; Hashimoto, Hiroya; Ogata, Katsuhisa; Kobayashi, Michio; Takada, Hiroto; Kuru, Satoshi; Kimura, Takashi; Nakamura, Akinori; Matsumura, Tsuyoshi
Abstract: Introduction/Aims: Due to muscular weakness and cardiopulmonary dysfunction, patients with muscular dystrophy (MD) have an increased risk of serious complications from coronavirus disease‐2019 (COVID‐19). Although vaccination is recommended, COVID‐19 vaccination safety and immunogenicity in these patients are unknown. We investigated reaction frequency, post‐vaccine antibody titers after two mRNA COVID‐19 vaccine doses, and clinical predictors of antibody response among patients with MD. Methods: We recruited 171 inpatients with MD receiving two BNT162b2 mRNA COVID‐19 vaccine doses from seven hospitals. Blood samples were obtained from 53 inpatients before the first dose and 28 to 30 days after the second dose, and antibody titers were measured. Results: Overall, 104 (60.8%) and 115 (67.6%) patients had side effects after the first and second doses, respectively. These were generally mild and self‐limited. Multiple logistic regression analysis showed that a bedridden state was associated with reduced side effects (odds ratio [OR] = 0.29; 95% confidence interval [CI], 0.12 to 0.71). The antibody titers of all participants changed from negative to positive after two vaccine doses. The geometric mean titer (GMT) of the inpatients was 239 (95% CI, 159.3 to 358.7). Older age (relative risk [RR] = 0.97; 95% CI, 0.95 to 0.99) and bedridden state (RR = 0.27; 95% CI, 0.14 to 0.51) were associated with a lower antibody titer. Patients with myotonic dystrophy type 1 (DM1) had a lower GMT than patients with other MDs (RR = 0.42; 95% CI, 0.21 to 0.85). Discussion: COVID‐19 vaccination is safe and immunogenic in inpatients with MD. Patients with DM1 appear to have a poorer COVID‐19 antibody response than those with other MDs.